External root resorption of a permanent tooth. Case study - Jacel Kotuła; Anna Kuc; Jakub Nawrocki; Alicja Babczyńska; Michał Sarul; Joanna Lis (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Introduction: External resorptions often occur as a lesion of inflammatory origin. The origin of the process begins on the side of the root cementum and goes towards the pulp of the tooth. The changes consist of the pathological loss of root cement, dentin, and bone surrounding the tooth. The dynamics of the process are enhanced by inflammatory or necrotic pulp changes. Aims: This study aimed to present contemporary views on the resorption of external tooth roots and the possibility of their treatment. Material and methods: The technique of observation and clinical and radiological diagnostics were used by the case-by-case method Result: Endodontic treatment was undertaken, consisting of chemo-mechanical preparation of the canal system and simultaneous obturation of the gutta percha canals with the AH + sealant and the BL thermal system. Conclusions: The applied treatment inhibited the progression of the resorption and led to the healing of periapical periodontitis.